Accessibility and implementation in the UK NHS services of an effective depression relapse prevention programme: learning from mindfulness-based cognitive therapy through a mixed-methods study - Jo Rycroft-Malone; Felix Gradinger; Heledd O Griffiths; Rebecca Crane; Andy Gibson; Stewart Mercer; Rob Anderson; Willem Kuyken (National Institute for Health Research, 2017)
Background: Depression affects as many as one in five people in their lifetime and often runs a recurrent lifetime course. Mindfulness-based cognitive therapy (MBCT) is an effective psychosocial approach that aims to help people at risk of depressive relapse to learn skills to stay well. However, there is an 'implementation cliff': access to those who could benefit from MBCT is variable and little is known about why that is the case, and how to promote sustainable implementation. As such, this study fills a gap in the literature about the implementation of MBCT. Objectives: To describe the existing provision of MBCT in the UK NHS, develop an understanding of the perceived costs and benefits of MBCT implementation, and explore the barriers and critical success factors for enhanced accessibility. We aimed to synthesise the evidence from multiple data sources to create an explanatory framework of the how and why of implementation, and to co-develop an implementation resource with key stakeholders. Design: A two-phase qualitative, exploratory and explanatory study, which was conceptually underpinned by the Promoting Action on Research Implementation in Health Services framework. Setting: UK NHS services. Methods: Phase 1 involved interviews with participants from 40 areas across the UK about the current provision of MBCT. Phase 2 involved 10 case studies purposively sampled with differing degrees of MBCT provision, and from each UK country. Case study methods included interviews with key stakeholders, including commissioners, managers, MBCT practitioners and teachers, and service users. Observations were conducted and key documents were also collected. Data were analysed using a modified approach to framework analysis. Emerging findings were verified through stakeholder discussions and workshops. Results: Phase 1: access to and the format of MBCT provision across the NHS remains variable. NHS services have typically adapted MBCT to their context and its integration into care pathways was also highly variable even within the same trust or health board. Participants' accounts revealed stories of implementation journeys that were driven by committed individuals that were sometimes met by management commitment. Phase 2: a number of explanations emerged that explained successful implementation. Critically, facilitation was the central role of the MBCT implementers, who were self-designated individuals who 'championed' implementation, created networks and over time mobilised top-down organisational support. Our explanatory framework mapped out a prototypical implementation journey, often over many years. This involved implementers working through grassroots initiatives and over time mobilising top-down organisational support, and a continual fitting of evidence, with the MBCT intervention, contextual factors and the training/supervision of MBCT teachers. Key pivot points in the journey provided windows of challenge or opportunity. Limitations: The findings are largely based on informants' accounts and, therefore, are at risk of the bias of self-reporting. Conclusions: Although access to MBCT across the UK is improving, it remains very patchy. This study provides an explanatory framework that helps us understand what facilitates and supports sustainable MBCT implementation. Future work: The framework and stakeholder workshops are being used to develop online implementation guidance. Funding: The National Institute for Health Research Health Services and Delivery Research programme.